Well-Being Workplace for Pt X Employees in Sidoarjo : Workplace Well-Being Pada Karyawan Pt X Di Sidoarjo - Intriyawati Agustin; Effy Wardati Maryam (Academia Open, 2022)
PT X employees in Sidoarjo still have workplace well-being problems such as being unable to adjust to the work environment, feeling that salaries have not been met to meet their daily needs and lack of appreciation for the achievements that have been given by employees. The purpose of this study was to determine the description of workplace well-being and the factors that affect workplace well-being in PT X employees in a quantitative descriptive manner. The population in this study were employees of PT X Sidoarjo as many as 920 employees. The sample used is 255 employees, based on an error rate of 5% in the table developed by Isaac and Michael. The sampling technique in this study is proportional random sampling. The data collection technique in this study used a psychological scale, namely the workplace well-being scale in the form of a used scale. The results of the validity test were obtained as many as 50 valid items from 52 items compiled. The reliability test showed that it was 0.938. Based on the results of the analysis showed that the workplace well-being in the high category was 58.4%, medium 41.6% and low 0%, meaning that the welfare of PT X Sidoarjo employees in the company was classified as good. Factors that affect workplace well-being are achievement (27.84%), self-evaluation (23.5%), feeling happy when getting support from others (21.18%), getting recognition from others (16 ,47%), and the last one is satisfied in doing work (11%).Keywords - Workplace Well-Being, Employees.